Mendorong Ambidexterity dalam Jejaring Kebijakan untuk Inovasi UKM di Pekanbaru - Ade Ria Nirmala (Al-Manar Journal of Economic and Social Studies, 2025)
SMEs are the main drivers of the local economy in Indonesia. However, limited resources and innovation capacity make it difficult for SMEs to develop in the era of disruption. The concept of ambidexterity—an organization's ability to balance exploration and exploitation—can be a strategic framework in public policy networks to encourage SME innovation. This study aims to conduct a systematic review of the ambidexterity literature in the context of policy networks and its relevance to strengthening SMEs in Pekanbaru. Using the systematic literature review (SLR) method, this article examines more than 50 recent scientific publications to formulate conceptual and practical implications. The results of the study reveal the importance of local institutional capacity, participatory leadership, and actor diversity as drivers of ambidexterity. This article concludes that collaborative network-based policies need to be designed by considering the balance of short-term and long-term strategies to strengthen SME competitiveness at the local level.